Occupational commitment and labor relations in firms: an empirical study in China - Yuan, Ling; Li, Jian (Chinese management studies, 2012)
Purpose - The purpose of this paper is to fill the gap in the existing literature regarding relationships between occupational commitment and labor relations in the Chinese context, particularly in Chinese firm settings.Design methodology approach - Based on well-defined concepts and instruments, the data were collected from 402 human resources (HR) workers in 35 firms, mainly located in Yangtze River Delta, Pearl River Delta and Hunan Province, China.Findings - The occupational commitment for HR workers in Chinese firms can be divided in four dimensions: affective commitment, normative commitment, accumulated costs and limited alternatives. There are positive interrelations between the four dimensions of occupational commitment and labor relations. Also, there is a significant correlation among the three-way interactive terms with labor relations.Research limitations implications - Although the results of this paper suggest that the four-dimensional model of occupational commitment can be employed to account the variation of labor relations in China, there is a need to use other samples and additional noted research design variables, e.g. organizational commitment and intent to leave one's job, to explore labor relations more comprehensively and deeply.Originality value - Theoretically, the paper serves as a pioneer research for indigenizing the concept of occupational commitment in the Chinese context, and fills the gap in the existing literature of the subjects being studied. Practically, the results and recommendations in the paper will be useful to those involved in the field of HR management in firms in China.